( 4 + X ) ² =
( 2a - 3 ) ² =
Soluções para a tarefa
Respondido por
1
Resposta:
(a + b)² = a² + 2ab + b²
(a - b)² = a²- 2ab + b²
Explicação passo-a-passo:
(4 + X) ² = 4² + 2 (4) (X) +x²
16 + 8x + X²
(2a - 3) = 2a² - 2(2a)(-3) + 3²
4a² - 12a + 9
(4+x)*2 = x*2+8x+16
(2a-3)*2 = 4a*2-12a+9
explicação passo a passo:
(4+x)*2
16+8x+x*2
x*2+8x+16
-------------------------------------------
(2a-3)*2
(2a)*2-2×2a×3+3*2
4a*2-12a+9
obs.: esse (*2) significa q é elevado a 2
Perguntas interessantes
Matemática,
9 meses atrás
História,
9 meses atrás
Geografia,
9 meses atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Pedagogia,
1 ano atrás
ENEM,
1 ano atrás
Contabilidade,
1 ano atrás
(4+x)*2 = x*2+8x+16
(2a-3)*2 = 4a*2-12a+9
explicação passo a passo:
(4+x)*2
16+8x+x*2
x*2+8x+16
-------------------------------------------
(2a-3)*2
(2a)*2-2×2a×3+3*2
4a*2-12a+9
obs.: esse (*2) significa q é elevado a 2